Sistem Informasi Penjualan Sparepart Berbasis Web sebagai Solusi Digitalisasi di Bengkel Ajeng Ratu Motor - Irwan Jaya; Pradipta, Anjar; Muh. Hajar Akbar (JISTech : Journal of Information Systems and Technology, 2024)
The rapid development of information technology has driven various sectors, including the automotive sector, to adopt digitalization to improve operational efficiency. This study aims to develop a Web-Based Spare Parts Sales Information System as a digitalization solution at Ajeng Ratu Motor Workshop. The system is designed to address the problems of inventory management and sales transactions, which were previously conducted manually. The study employs the Waterfall method, which includes stages of requirement analysis, system design, implementation, testing, and maintenance. System testing was carried out using the Black Box method, and the results show that the system functions as expected. The main features of the system include stock management modules, sales transaction modules, and reporting modules. The implementation of this system improves operational efficiency, reduces recording errors, and speeds up the stock management process. Additionally, the system benefits customers by allowing them to check spare parts availability in real-time. Therefore, this information system provides an effective solution for business process digitalization in workshops, particularly in spare parts sales management